Probing the Dynamics of Topologically Protected Charged Ferroelectric Domain Walls with the Electron Beam at the Atomic Scale - Jones, Lewys (My University, 2020)
Dynamic charged ferroelectric domain walls (CDWs) overturn the classical idea that our electronic circuits need to consist of fixed components of hardware.[1,2] With their own unique electronic properties and exotic functional behaviours all confined to their nanoscale width, DWs represent a completely new 2D material phase.[3-5] The most exciting aspect of CDWs in single crystals is that they can be easily created, destroyed and moved simply by an applied stimulus. The dynamic nature of CDWs gives them the edge over other novel systems and may lead to them being the next promising disruptive quantum technology. This is an area of research at its very early stages with endless possible applications. However, to harness their true potential there is a great deal of the fundamental physics yet to uncover. As the region of interest (CDW) is atomically thin and dynamic, it is essential for the physical characterisation to be at this scale spatially and time-resolved.
PUBLISHED